Diagnostic agreement between three point-of-care glucose and β-hydroxybutyrate meters and reference laboratory methods in stingrays - Dannemiller, Nicholas G.; Cray, Carolyn; Westmoreland, Lori S.; Christiansen, Emily F. (Frontiers in Veterinary Science, 2023)
Point-of-care (POC) glucose and β-hydroxybutyrate (β-HB) meters can potentially provide rapid insight into an elasmobranch's metabolic state in clinical and field research settings. This study evaluated the diagnostic agreement of three commercial POC meters against reference laboratory methods for glucose and β-HB concentrations in stingrays. Blood was collected during anesthetized exams from twenty-eight stingrays representing four species: cownose rays (Rhinoptera bonasus), Atlantic stingrays (Hypanus sabina), southern stingrays (Hypanus americanus), and yellow stingrays (Urobatis jamaicensis). Glucose and β-HB concentrations were measured with each POC meter using whole blood and plasma; in parallel, plasma glucose and β-HB concentrations were measured via reference laboratory methods. Agreement between POC meters and reference laboratory methods was assessed using Bland-Altman methods, Passing-Bablok regression, observed total error, percent relative error, and linear mixed effect models. Plasma glucose and β-HB concentrations determined by reference laboratory methods ranged from < 20-63 mg/dL and 0.05-5.38 mmol/L, respectively. One human POC meter-the Precision Xtrashowed the greatest agreement with reference laboratory methods when measuring glucose with whole blood [mean bias and 95% CI: 0 (-3-4) mg/dL] and β-HB with plasma [mean bias and 95% CI: 0.1 (-0.04-0.2) mmol/L]. Stingray sex, weight, buffy coat, and packed cell volume did not significantly affect the agreement between POC meters and reference laboratory methods. Across all three POC meters, mean bias and imprecision for plasma β-HB concentrations were relatively small (0-0.1 mmol/L and 0%, respectively). Utilizing POC meters to measure glucose and β-HB in stingrays may be viable when reference methods are unavailable.